Adaptive reuse of underused buildings a sustainable strategy for urban reoccupation in downtown Vitória (Brazil) - Longue, Iago (Universidad de Lima. Carrera de Arquitectura, 2021)
DOI: https://doi.org/10.26439/limaq2021.n007.5179 The production model of the built environment applied to the contemporary urban context has presented a series of dysfunctions that highlight the unsustainability of this system. Among these dysfunctions, there is an intense urban dispersion, which requires greater spending on mobility infrastructure. In addition, the inadequate management of the built space, materialized in the set of underused buildings that permeate the urban context of central neighborhoods in medium and large cities, affects the socio-environmental dynamics of the place. In this sense, the present work aims to research the impact of underused buildings in the urban fabric of downtown Vitória (Brazil), as well as its recovery for the socio-environmental dynamics that develop in such region. The results show that the strategies help the resumption of urban dynamism and allow the reuse of the mobility and real estate infrastructures existing in the place. reutilización adaptativa, sostenibilidad, medio construido, intervención urbana adaptive reuse, sustainability